Design and Analysis of Microstrip Line Feed C-Shape Frequency Reconfigurable Antenna for Wireless Application - Santosh Kumar Tripathi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this work, a frequency-reconfigurable C- shape multiband antenna using a 1.6 mm FR-4 substrate and a partial ground plane is presented. Frequency reconfiguration is accomplished in simulation using the lumped element switch. The proposed antenna has been simulated using CST Studio Suite 2022. The provided antenna is capable of operating in four modes, depending on the state of the switch. The suggested antenna functions in dual band in mode 1-3 and triple band in mode 4. The resonant frequencies of antenna are 2.19 GHz, 2.44 GHz, 2.98 GHz, 3.01 GHz, 5.67 GHz, 7.53 GHz, 7.59 GHz, 7.71 GHz and 8.17 GHz, and corresponding bandwidths are 0.36 GHz, 0.46 GHz, 0.71 GHz, 0.74 GHz, 1.56 GHz, 2.92 GHz, 4.17 GHz, 2.62 GHz and 1.56 GHz. It can be used for numerous applications such as UMTS, Bluetooth, WLAN, high-frequency LTE, S-DMB, WiMAX, C and X band applications.